Impact of social experience on customer purchase decision in the social commerce context. Issue 1 (21st February 2020) - Handarkho, Yonathan Dri
Abstract : Purpose: This study aims to examine the factor of social experience influencing an individual's purchase decision in the social commerce (SC) environment by proposing a model developed based on the social impact theory. The proposed model consists of the number, closeness and tie strength of the influencing factor and the receiver. Design/methodology/approach: A total of 288 responses were collected from Indonesian SC users to validate the theoretical model, which consists of perceived herd behavior, peer communication, emotional support, parasocial interaction and subjective norms. This study also explores the moderating effects of gender, age, experiences and occupations on the direct effect of model variables, which affect the individual's intention to purchase in SC. Findings: The results of this study showed that parasocial interaction is the strongest determinant of intention to purchase in SC, followed by perceived herd behavior and peer communication. However, the direct effect of subjective norms and emotional support were found insignificant in this study. For moderating effects, only gender and occupation were significant in terms of the immediate effect of peer communication, perceived herd behavior and subjective norms on intention to purchase. Originality/value: The study contributes to theory in the form of insight on immediate effect and the exploratory investigation of moderating effects. It also contributes to practice by suggesting several practical actions based on the findings designed to achieve the objective of improving customers' intention to purchase in SC.